2013
DOI: 10.1002/wrcr.20198
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of exchange between groundwater and surface water based on high‐frequency direct measurements of seepage at the sediment‐water interface

Abstract: [1] Seepage at the sediment-water interface in several lakes, a large river, and an estuary exhibits substantial temporal variability when measured with temporal resolution of 1 min or less. Already substantial seepage rates changed by 7% and 16% in response to relatively small rain events at two lakes in the northeastern USA, but did not change in response to two larger rain events at a lake in Minnesota. However, seepage at that same Minnesota lake changed by 10% each day in response to withdrawals from evap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…In addition, Diem et al (2014) recently showed that groundwater residence times are also strongly affected by the estimation of in-stream longitudinal water level distributions. These results are due to the fact that stream-aquifer exchange rates adapt very quickly to changes in surface water levels (Koussis et al, 2007;Maier and Howard, 2011;Rosenberry et al, 2013).…”
Section: The Conductance Model At the Regional Scalementioning
confidence: 99%
“…In addition, Diem et al (2014) recently showed that groundwater residence times are also strongly affected by the estimation of in-stream longitudinal water level distributions. These results are due to the fact that stream-aquifer exchange rates adapt very quickly to changes in surface water levels (Koussis et al, 2007;Maier and Howard, 2011;Rosenberry et al, 2013).…”
Section: The Conductance Model At the Regional Scalementioning
confidence: 99%
“…Crusius et al, 2005;Santos et al, 2009;Taniguchi, 2002). Similarly, rapid variations in groundwater fluxes have been observed in lakes in response to factors such as seiching and precipitation (Rosenberry et al, 2013). However, there is little known about the variations and dynamics in groundwater discharge over time scales of days to weeks in wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…These increases were mainly ascribed to local water circulations driven by wind waves (Figure 4). Rosenberry et al [46] reported for the Great Salt Lake (USA) that there may be infiltration/exfiltration reversals due to waves, as well as reversals in the flow direction across the sediment-water interface. Similarly, Longuet-Higgins [47], Lenkopane et al [48], Wilson and Gardner [14], and Gibbes et al [49] reported that the mean onshore pressure gradient due to wave run up drives a groundwater circulation within the beach zone.…”
Section: Discussionmentioning
confidence: 99%